Perancangan Alat Ukur Kadar Alkohol Menggunakan Sensor Mq-3 Berbasis Mikrokontroler Atmega16 - Surya Merta, I Gede; Widagda, I Gusti Agung; Alit Paramarta, Ida Bagus (BULETIN FISIKA, 2017)
It has been successfully designed an alcohol levels measuring instrument using MQ-3 sensor. The detected alcohol levels processed to be displayed on GUI Visual Basic 6.0 through several circuits, the sensor circuit, the Atmega16 microcontroller minimum system, 5V voltage regulator circuits, CH340 serial communication module and GUI Visual Basic 6.0. The entire circuit is powered by 5VDC regulator circuit. The measurement range of this instrument measures alcohol level in the range 0% to 70%, the levels measured by the instrument will be classified according to the regulations sets by Indonesian government. The instrument works by employing the characteristics of the MQ-3 sensor which has proportional voltage change with alcohol levels that is detected. The Atmega16 circuit is the main unit for data processing, the microcontroller performs the analog to digital data conversion and estimates this digital data into matching alcohol levels. Alcohol content data that processed is displayed on the GUI Visual Basic 6.0 through serial communication module CH340. Detected alcohol levels by this instrument compared with the alcohol levels of sample is match by 99.57%.